Green credit policy's impact on polluting firms' market performance: the role of financing constraints - Wang, Zhongshuai; Bian, Baocheng; Zhu, Chunqian; Lu, Yuchen; Wang, Jun (Frontiers in Environmental Economics, 2025)
As the contradiction between China's economic growth and energy consumption becomes increasingly prominent, how to guide resource allocation towards green sectors through financial policies has emerged as a critical issue for achieving sustainable development. As a key instrument integrating environmental regulation with financial control, green credit policies require in-depth examination to determine their effectiveness in directing credit resources, improving corporate environmental behavior, and promoting economic transformation. This study employs data from A-share listed companies between 2008 and 2023, utilizing the 2012 issuance of the Green Credit Guidelines as a natural experiment. It applies a Difference-in-Differences (DID) approach to examine the impact of green credit policies on the market performance of polluting enterprises and their underlying mechanisms. Findings reveal that green credit policies significantly suppress the market performance of heavily polluting enterprises, with this effect primarily channeled through heightened financing constraints, particularly pronounced among privately owned firms. Heterogeneity analysis indicates marked variations in policy impact across firms differing in industry concentration, possession of green innovations, and regional development levels. Polluting enterprises in highly concentrated industries, those possessing green innovations, and those located in eastern regions experience relatively lesser impacts. These findings not only validate the effectiveness of green credit policies in optimizing credit resource allocation but also provide novel empirical evidence for understanding the synergistic mechanisms between financial policies and environmental governance. The study further refines the differentiated implementation mechanisms for green credit policies, avoiding the excessive impact of a ‘one-size-fits-all' approach on certain enterprises, and demonstrates the benefits of considering different perspectives and levels of analysis.